Age-specific associations between intergenerational support from children and depression in middle-aged and elderly Chinese: results from the China health and retirement longitudinal study - Lu, Yongbo; Zhang, Jingya; Zhou, Zongyang; He, Rongxin; Zhu, Bin; Mao, Ying (Frontiers in Psychology, 2025)
ObjectivesTo assess the age-specific associations between intergenerational support from children and depression in middle-aged and elderly Chinese.MethodsIn total, 11,398 adults aged ≥45 who participated in the China Health and Retirement Longitudinal Study (CHARLS) 2018 were included. Depression was assessed using the Center for Epidemiological Studies Depression Scale (CES-D). Logistic regression analysis was performed to examine the effects of offline companionship, online companionship, money support, and goods support from children on the depression status of middle-aged and elderly people.ResultsAmong people aged 80 and above, offline companionship is associated with a reduced risk of depression (OR = 0.573, 95% CI: 0.372, 0.883). However, online companionship may be associated with an increased risk of depression in individuals aged 45–60. Money support was found to have a positive association with depression in individuals aged 45–60 (OR = 1.182, 95% CI: 1.005, 1.389), but a negative association in those aged 60–80 (OR = 0.767, 95% CI: 0.632, 0.930). Goods support is associated with a decreased risk of depression in individuals aged 45–80.ConclusionFor individuals aged 45–60, children can offer valuable goods support to mitigate parental depression. In the 60–80 age group, both money and goods support are essential. For those over 80, increased offline companionship is recommended.